Inhibition of carbohydrate hydrolyzing enzymes by a potential probiotic Levilactobacillus brevis RAMULAB49 isolated from fermented Ananas comosus - Martiz, Reshma Mary; Kumari V. B., Chandana; Huligere, Sujay S.; Khan, Mohd Shahnawaz; Alafaleq, Nouf Omar; Ahmad, Saheem; Akhter, Firoz; Sreepathi, Navya; P., Ashwini; Ramu, Ramith (Frontiers in Microbiology, 2023)
The potential probiotic isolate Levilactobacillus brevis RAMULAB49 was isolated from fermented pineapple considering the fact that such fruits are least explored for their probiotic properties. On the other hand, it is a well-known fact that probiotics take part in balancing gut microbiota, which in turn maintains human physiology and metabolism. By interconnecting these two aspects, the present study aimed to isolate lactic acid bacteria (LAB) with potential antidiabetic properties. All the collected isolates were initially screened for microscopic and biochemical properties. Among the isolates, RAMULAB49 was selected which was Gram-positive, catalase-negative, tolerant to phenol and gastrointestinal conditions, and expressed hydrophobicity (65.71%) with xylene. The autoaggregation ability of the isolate was 77.76%, and the coaggregation activity against Micrococcus luteus, Pseudomonas aeruginosa, and Salmonella enteric typhimurium was maximum in the cell-free supernatant. The isolate was susceptible to kanamycin, vancomycin, methicillin, and rifampicin. The probiotic strain was negative for hemolytic and DNase enzyme activity, thus considered safe. The antioxidant ability of the isolate on ABTS and DPPH was 74.85% and 60.51%, respectively with 109 CFU/mL of bacterial cells. A high inhibition of α-amylase (56.19%) and α-glucosidase (55.69%) was observed in the cell-free supernatant (in vitro). In silico studies also substantiate this inhibition using extracted organic acids (LC-MS). Pa value of citric acid, hydroxycitric acid, and malic acid was found to be greater pharmacological activity than that of the other compounds. The results prove that Levilactobacillus brevis RAMULAB49 isolated from fermented pineapple acts as a promising antidiabetic drug.